OPTIMIZING FISHERY BY-PRODUCTS : FISH BONE (PANGASIUS HYPOPHTHALMUS) MEAL WITH TEXTURE STABILITY FROM YOUNG JACKFRUIT - Ariska, Iis; Nugroho, Alief; Suseno, Suseno; Listyaningrum, Niken Prawesti (Politeknik Kelautan dan Perikanan Karawang, 2026)
Several marine product processing sectors still produce by-products that are not optimally managed and utilized, including Patin fish bones (Pangasius hypophthalmus) as a by-product of marine product processing. In this era that demands sustainability, waste management has become a crucial issue. It is no longer about how waste can be destroyed, but how waste management has an impact. From a mineral perspective, patin fish bones are rich in calcium (Ca) and phosphorus (P), which play an important role in bone and tooth formation, making them a potential source for value-added products. Patin fish bone floss is a value-added product as an innovation in the utilization of Patin fish bones, which in its manufacture uses natural additives, one of which is young jackfruit. The dietary fiber in young jackfruit helps maintain the dry texture of the floss because the fiber in young jackfruit can absorb oil content, thereby increasing stability during cooking. The results of the study also prove that the average sensory score was 8.5 for shredded fish with the addition of young jackfruit, and 8 for shredded fish without the addition of young jackfruit. This proves that the addition of young jackfruit greatly affects the production of shredded patin fish bones. Not only does it have health benefits, but patin fish bone abon as an innovative product also has added value in the economic sector, namely as a business idea with low production costs and a social impact through the creation of jobs.